Experiences of Breastfeeding Among First Time Teenage Mothers - ฉิ่งเล็ก วิโรจน์; เกตุอินทร์ วารุณี; ศรียะศักดิ์ อัจฉราวดี (Princess of Naradhiwas University Journal, 2018)
The qualitative study aimed to explore and describe the experiences of breastfeeding among first time teenage mothers. Twenty first time teenage mothers who breastfeeding more than one months, residing in Phetchaburi province were interviewed. Content analysis was used to analyze interview transcripts with the teenage mothers. The results show that factors supporting breastfeeding successful were perceiving the benefits of breastfeeding, having a breastfeeding model, and enabling in breastfeeding. Barriers to breastfeeding successful were influenced from their families, health and nipples problems, and a lack of understanding of breastfeeding. Teenage mothers needed help from family and health care provider for successful in breastfeeding. Recommendation for this study is to include teenage grandparents and promote her family to participate in breastfeeding class. This will help to success in exclusive breastfeeding among teenage mothers.